CUASI DOMINANCIA ESTOCÁSTICA. APLICACIONES - Almaraz-Luengo, Elena (Revista Colombiana de Estadística, 2011)
The aim of this work is to show that on certain ocasions classic decision rules used in the context of options (Stochastic Dominance criteria and Mean-Variance rules) do not provide a selection of one specific option over the other, therefore, the need of working with other criteria that can help us in our choice. We place special interest in economic and financial applications.